2018
DOI: 10.1111/bre.12272
|View full text |Cite
|
Sign up to set email alerts
|

Refining stratigraphy and tectonic history using detrital zircon maximum depositional age: an example from the Cerro Fortaleza Formation, Austral Basin, southern Patagonia

Abstract: The north–south trending, Late Cretaceous to modern Magallanes–Austral foreland basin of southernmost Patagonia lacks a unified, radiometric, age‐controlled stratigraphic framework. By simplifying the sedimentary fill of the basin to deep‐marine, shallow‐marine and terrestrial deposits, and combining 13 new U‐Pb detrital zircon maximum depositional ages (DZ MDAs) with published DZ MDAs and U‐Pb ash ages, we provide the first attempt at a unified, longitudinal stratigraphic framework constrained by radiometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0
19

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 52 publications
(223 reference statements)
7
57
0
19
Order By: Relevance
“…Based on outcrop, core, and seismic observations, clastic deposition appears to have been continuous during Cretaceous time, with no significant basinwide hiatus in deposition from the end of Jurassic extension through the transition to compression and Cretaceous flexural subsidence (Figs. 2B and 4;Wilson, 1991;Arbe, 2002;Sickmann et al, 2018). The only apparent basinwide unconformity occurs between Upper Cretaceous and Middle Eocene deposits (Fig.…”
Section: Geologic Backgroundmentioning
confidence: 95%
See 2 more Smart Citations
“…Based on outcrop, core, and seismic observations, clastic deposition appears to have been continuous during Cretaceous time, with no significant basinwide hiatus in deposition from the end of Jurassic extension through the transition to compression and Cretaceous flexural subsidence (Figs. 2B and 4;Wilson, 1991;Arbe, 2002;Sickmann et al, 2018). The only apparent basinwide unconformity occurs between Upper Cretaceous and Middle Eocene deposits (Fig.…”
Section: Geologic Backgroundmentioning
confidence: 95%
“…Depositional systems associated with this transition indicate shallower water depths in the north compared to southern temporal equivalents due to a long-lived, southward-dipping depositional gradient in the basin (Figs. 2B and 4;Arbe, 2002;Sickmann et al, 2018). Due to lithospheric weaknesses that were inherited from the extensional phase of the basin, the Magallanes-Austral Basin foredeep appears to have been deeply subsided and "pinned" for an extended period of time with a subdued forebulge (Fosdick et al, 2014).…”
Section: Geologic Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Tectonics be the most robust method (Orme et al, 2015;Sickmann et al, 2018). We used this algorithm and found that it produced reasonable results for the Raggyorcaka samples (Figures 3, S2, and S3 and Table 2).…”
Section: 1029/2019tc005589mentioning
confidence: 97%
“…The South American record is the most extensive, diverse and abundant, with six taxa named to date: Aoniraptor libertatem [37], Orkoraptor burkei [33], Megaraptor namunhuaiquii [32,38,39], Murusraptor barrosaensis [30,40,41], Aerosteon riocoloradensis [28], and Tratayenia rosalesi [42]. Numerous fragmentary specimens have also been reported from South America (see supplementary table 7 in [1]), which include the oldest (Albian [43]) and the youngest (Campanian [44]).…”
Section: Introductionmentioning
confidence: 99%